Inducible Mtld expression facilitated the introduction of the mannitol synthesis pathway in Synechococcus elongatus PCC 7942 - Sun, Jiahui; Cui, Jinyu; Xu, Xuejing; Tang, Jinhui; Sun, Huili; Liu, Xiangxiao; Yuan, Xiangyi; Luan, Guodong; Lu, Xuefeng (Frontiers in Bioengineering and Biotechnology, 2025)
Mannitol is a valuable sugar alcohol, extensively used across various industries. Cyanobacteria show potential as future platforms for mannitol production, utilizing CO2 and solar energy directly. The proof-of-concept has been demonstrated by introducing a two-step pathway in cyanobacteria, converting fructose-6-phosphate to mannitol-1-phosphate and sequentially to mannitol. However, recombinant strains generally faced issues of genetic instability or low titers, consequently affecting the long-term mannitol production. In this work, the construction strategy for engineering mannitol production in Synechococcus elongatus PCC 7942, based on commonly adopted pathway comprising mannitol-1-phosphate dehydrogenase (Mtld) and mannitol-1-phosphatase (M1Pase), was optimized. The results demonstrated that the sequential introduction of m1p and mtld was required to obtain mannitol-producing strains. We further manipulated the abundances of Mtld with a theophylline dose-responsive riboswitch approach, and by combining it with the overexpression of m1p, we successfully obtained a recombinant strain producing 1.5 g/L mannitol under optimal conditions, the highest cyanobacterial yield to date. In addition, the controlled expression of mtld was demonstrated to remarkably augment the genetic stability of the mutant under long-term culturing circumstances, which continued to secrete mannitol after more than 2 months of cultivation without the addition of theophylline, and the mannitol biosynthesis operon did not undergo any spontaneous mutation. The findings in this work provided novel insights into the area of cyanobacteria mannitol metabolism engineering, and would inspire researchers to construct strains with different gene regulatory strategies for efficient photosynthetic biosynthesis.